The Effect of Entrepreneurial Behavior and Competency of Entrepreneurship on Ornamental Plant Business Performance in Bogor City - Syahroni; Wahyu Budi Priatna; Burhanuddin (School of Business, IPB University (SB-IPB), 2021)
The ornamental plant business is a business dominated by MSEs, so it has a vital role in economic development and growth. The largest ornamental plant production centre city in West Java Province is Bogor City. This is an opportunity to develop an ornamental plant business in Bogor City, which can be carried out by entrepreneurial behaviour and entrepreneurial competence of ornamental plant entrepreneurs. This study aimed to analyze the influence of entrepreneurial behaviour and entrepreneurial competence on the performance of ornamental plants in the city of Bogor. Respondents in this study were ornamental plant entrepreneurs with several 100 people who were determined by the conventional method. Data analysis in this study used the Structural Equation Model (SEM) with the help of AMOS 23 software. The results showed that entrepreneurial behaviour had a positive and significant effect on ornamental plants' performance with a coefficient value of 0,63 and a t-statistic value of 3,52. Besides, entrepreneurial competence also has a positive and significant effect on ornamental plants' performance, with a coefficient of 1,12 and a t-value of 14,61. This means that any increase in entrepreneurial behaviour and entrepreneurial competence will improve the performance of ornamental plants in the city of Bogor.